2023
DOI: 10.1186/s12943-023-01801-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of tumor resistance to radiotherapy

Abstract: Background Cancer is the most prevalent cause of death globally, and radiotherapy is considered the standard of care for most solid tumors, including lung, breast, esophageal, and colorectal cancers and glioblastoma. Resistance to radiation can lead to local treatment failure and even cancer recurrence. Main body In this review, we have extensively discussed several crucial aspects that cause resistance of cancer to radiation therapy, including rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(37 citation statements)
references
References 259 publications
0
37
0
Order By: Relevance
“…Immunofluorescence imaging revealed that treating H-4T1 cells with 4 Gy IR induced only a negligible increase in cellular γ-H2AX levels, which indicated the insufficient capability of low-dose IR to induce DNA double-strand breaks and was also consistent with the observations in previous reports. 55,56 In contrast, H-4T1 cells in the TCPP@Hf-TK-PEG-PAMAM-FA+IR group showed strong significant γ-H2AX fluorescence in the nucleus region, attributed to the strong photoelectric effect of Hf 4+ ions that could enhance the IR dose deposition in tumor tissues. 57 Notably, H-4T1 tumors with combination TCPP-TK-PEG-PAMAM-FA@siHIF-1α+IR treatment also showed obvious enhancement in γ-H2AX signals.…”
Section: (G) Flow Cytometry Analysis On the Lds Abundance In H-4t1 Ce...mentioning
confidence: 95%
“…Immunofluorescence imaging revealed that treating H-4T1 cells with 4 Gy IR induced only a negligible increase in cellular γ-H2AX levels, which indicated the insufficient capability of low-dose IR to induce DNA double-strand breaks and was also consistent with the observations in previous reports. 55,56 In contrast, H-4T1 cells in the TCPP@Hf-TK-PEG-PAMAM-FA+IR group showed strong significant γ-H2AX fluorescence in the nucleus region, attributed to the strong photoelectric effect of Hf 4+ ions that could enhance the IR dose deposition in tumor tissues. 57 Notably, H-4T1 tumors with combination TCPP-TK-PEG-PAMAM-FA@siHIF-1α+IR treatment also showed obvious enhancement in γ-H2AX signals.…”
Section: (G) Flow Cytometry Analysis On the Lds Abundance In H-4t1 Ce...mentioning
confidence: 95%
“…139 The study showed that aberrant metabolism was closely related to the drug-resistant generation. 140 The resistance of cancer to radiation therapy was closely related to metabolism disturbance, 141 extent. 142,143 Recent insights collectively reveal that ferroptosis is intricately regulated by multiple cellular metabolism pathways.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…The study showed that aberrant metabolism was closely related to the drug-resistant generation . The resistance of cancer to radiation therapy was closely related to metabolism disturbance, although ferroptosis had addressed chemotherapy resistance to some extent. , Recent insights collectively reveal that ferroptosis is intricately regulated by multiple cellular metabolism pathways . Immunotherapy has emerged as a major therapeutic modality in oncology; , however, immune escape was a huge challenge to deal with .…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…In radiation therapy, the high-energy radiation can kill tumor cells and also presents great side effects on normal cells. 4 In chemotherapy, the primary and metastatic tumors can be killed, but tumors become resistant to chemical drugs and are prone to relapse. 5 Therefore, the development of new methods and drugs for accurate diagnosis and targeted therapy is an urgent need to solve the world's tumor problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tumor may be removed incompletely, and surgical resection of deep vital organs is risky and traumatic and is unable to inhibit metastasis. In radiation therapy, the high-energy radiation can kill tumor cells and also presents great side effects on normal cells . In chemotherapy, the primary and metastatic tumors can be killed, but tumors become resistant to chemical drugs and are prone to relapse .…”
Section: Introductionmentioning
confidence: 99%